Synthesis of New Series of Pyrazoline, and Study their Kinetics and Reaction Mechanism - Kaka, Kosrat N.; Taher, Salam G.; Hamad, Wali M.; Ibrahim, Aram H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
A new series of novel pyrazoline compounds were synthesized by addition of thiosemicarbazide to the 2,6-dibenzylidenecyclohexanone (Chalcone) and its para substituted derivatives. This study was conducted for four purposes. Firstly, a series of five membered ring pyrazoline compounds were synthesized and the structure of all new products obtained are supported by spectral data (1H-NMR, 13CNMR, IR and UV-Vis.), and the effect of substituents were studied. Secondly, the reaction kinetics of the new synthesized compounds were studied to investigate the reaction mechanism pathway and order of the reaction; it was found that, the reaction undergoes via Claisen route of mechanism with first-order reaction. Thirdly, the thermodynamics of the reaction were studied, the rate of the reaction, Arrhenius parameters (A), and thermodynamic parameters for activation includes (free energies (Ea), entropies (ΔS#), and Gibbs free energy (ΔG#) were estimated. Finally, the compensation effect was also studied, and found the same pathway for all of the synthesized pyrazoline compounds.